ANALISIS SEMIOTIKA ROLAND BARTHES DALAM NOVEL SEPORSI MIE AYAM SEBELUM MATI KARYA BRIAN KHRISNA - Hanna Puspita Prisia Simanjuntak; Dwi Leoni, Tessa; Habibah, Siti; Irawan, Dody; Lolita, Asri; Patria, Robby (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe Roland Barthes’ semiotic codes, consisting of hermeneutic code, semic code, symbolic code, proairetic code, and cultural code, found in the novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna. This research employed a qualitative approach with a descriptive method. The source of data in this study was the novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna, while the research data consisted of narrative and dialogue quotations containing Roland Barthes’ five semiotic codes. The data were collected through reading and note-taking techniques by thoroughly reading the novel, identifying semiotic signs, and classifying the data based on the types of codes found. The results showed that the novel contains five semiotic codes proposed by Roland Barthes, namely hermeneutic code, semic code, symbolic code, proairetic code, and cultural code. The hermeneutic code was found through questions, conflicts, and uncertainties experienced by the main character, which create enigmas regarding the meaning of life. The semic code appeared through connotative signs in the form of metaphors and expressions that represent the main character’s psychological conditions, such as loneliness, low self-esteem, and self-acceptance. The symbolic code was identified through symbols such as medicine, cats, chicken noodles, kites, teak trees, trains, and candle flames, which represent deeper meanings related to life, hope, and personal transformation. The proairetic code was found through the actions of the characters that develop the storyline and illustrate the transformation of the main character. Meanwhile, the cultural code was found through popular cultural references, language use, social habits, and values that exist within society. Based on the findings, it can be concluded that the five semiotic codes of Roland Barthes are interconnected in constructing the meaning of the novel, particularly in portraying the main character’s journey from despair toward the process of rediscovering hope and the meaning of life.